Cardiac Fibroblasts as a Support for Endothelial Cell Sprout Formation in Engineered Cardiac Tissue. - Twardowski, Rachel. (2017)
Abstract: Cardiac tissue engineering offers a promising approach to regenerating post-MI myocardial tissue; however, a primary impediment in tissue engineering lies in the inability to adequately vascularize a tissue scaffold. Cardiac tissue constructs require a closer proximity to a nutrient and blood supply than many other tissues due to the higher metabolic demands of myocardium, further decreasing the required distance to a capillary bed. It is known that endothelial cells (ECs) require a support cell to form mature patent lumens both in vivo and in vitro, and it has been demonstrated that pericytes, vascular smooth muscle cells and mesenchymal stem cells (MSCs) are able to support the formation of mature tubules/vessels. Cardiac fibroblasts (CFs) provide important electrical and mechanical components to the myocardial tissue and are present in the native cardiac cell population, but to date have not been sufficiently studied for their role in angiogenesis in heart. Three different approaches were used to study the ability of CFs to aid in the formation of EC sprouts: 1) varying the co-culture ratio of neonatal CFs to ECs to best match the in vivo conditions, while comparing the results to EC sprout formation in MSC co-cultures, 2) studying the differences of EC proliferation and sprout formation in co-culture with CFs at different developmental life points: fetal, neonatal and adult and 3) the use of a decellularized vessel as a central conduit for angiogensis in a fibrin construct. As a model of myocardial tissue, we co-cultured different concentrations of various cell types in fibrin hemispheres in appropriate combinations of their specific media to determine the optimal sprout formation through DNA analysis, flow cytometry and immunohistology (IH). Our hypothesis was that cardiac fibroblasts can support endothelial cell sprout formation as well or better than mesenchymal stem cells, which are considered to be a "gold standard" for the stabilization of EC sprouts in engineered tissues. Our results indicated that ECs tended to form longer and more numerous sprouts in culture with neonatal CFs, but formed more multi-cellular sprouts in culture with MSCs, which is more indicative of the in vivo process. Additionally, we found that EC proliferation was best when cultured with neonatal and adult CFs over the proliferation rate with fetal CFs. In summary, cardiac fibroblasts are able to provide a support for the formation of endothelial cell sprouts and could aid in the eventual vascularization of a cardiac tissue scaffold.; Thesis (M.S.)--Tufts University, 2012.; Submitted to the Dept. of Biomedical Engineering.; Advisor: Lauren Black III.; Committee: David Kaplan, and Ira Herman.; Keyword: Biomedical engineering.